Risk factors for perinatal mortality in Murmansk County, Russia: a registry-based study - Anna A. Usynina; Andrej M. Grjibovski; Alexandra Krettek; Jon Øyvind Odland; Alexander V. Kudryavtsev; Erik Eik Anda (Taylor & Francis Group, 2017)
Background: Factors contributing to perinatal mortality (PM) in Northwest Russia remain unclear. This study investigated possible associations between selected maternal and fetal characteristics and PM based on data from the population-based Murmansk County Birth Registry. Objective: This study investigated possible associations between selected maternal and fetal characteristics and PM based on data from the population-based Murmansk County Birth Registry. Methods: The study population consisted of all live- and stillbirths registered in the Murmansk County Birth Registry during 2006-2011 (n = 52,806). We excluded multiple births, births prior to 22 and after 45 completed weeks of gestation, infants with congenital malformations, and births with missing information regarding gestational age (a total of n = 3,666) and/or the studied characteristics (n = 2,356). Possible associations between maternal socio-demographic and lifestyle characteristics, maternal pre-pregnancy characteristics, pregnancy characteristics, and PM were studied by multivariable logistic regression. Crude and adjusted odds ratios with 95% confidence intervals were calculated. Results: Of the 49,140 births eligible for prevalence analysis, 338 were identified as perinatal deaths (6.9 per 1,000 births). After adjustment for other factors, maternal low education level, prior preterm delivery, spontaneous or induced abortions, antepartum hemorrhage, antenatally detected or suspected fetal growth retardation, and alcohol abuse during pregnancy all significantly increased the risk of PM. We observed a higher risk of PM in unmarried women, as well as overweight or obese mothers. Maternal underweight reduced the risk of PM. Conclusions: Our results suggest that both social and medical factors are important correlates of perinatal mortality in Northwest Russia.